2016
DOI: 10.1080/19420862.2015.1128605
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the ability of the human IgG1 allotypes G1m3 and G1m1,17 to stimulate T-cell responses from allotype matched and mismatched donors

Abstract: The immunogenicity of clinically administered antibodies has clinical implications for the patients receiving them, ranging from mild consequences, such as increased clearance of the drug from the circulation, to life-threatening effects. The emergence of methods to engineer variable regions resulting in the generation of humanised and fully human antibodies as therapeutics has reduced the potential for adverse immunogenicity. However, due to differences in sequence referred to as allotypic variation, antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The allotype abundance was found to mirror those previously reported for Caucasian populations, in which the G1m3-allele is known to be predominant ( 10 , 15 , 32 , 33 ). Interestingly, the frequency of donors homozygous for G1m3 (45.4%) reported for a larger study (570 community blood donors) coincided with the G1m3-distribution determined for the X001 study ( 29 ). It is important to note that abundance of different G1m phenotypes and allotype differ in other ethnicities (e.g., Asian and African populations) for which many of the larger HIV vaccine trials are currently conducted, and these protocols will need to be confirmed in these ethnicities in the future.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The allotype abundance was found to mirror those previously reported for Caucasian populations, in which the G1m3-allele is known to be predominant ( 10 , 15 , 32 , 33 ). Interestingly, the frequency of donors homozygous for G1m3 (45.4%) reported for a larger study (570 community blood donors) coincided with the G1m3-distribution determined for the X001 study ( 29 ). It is important to note that abundance of different G1m phenotypes and allotype differ in other ethnicities (e.g., Asian and African populations) for which many of the larger HIV vaccine trials are currently conducted, and these protocols will need to be confirmed in these ethnicities in the future.…”
Section: Discussionsupporting
confidence: 77%
“…We wished to assess whether IgG-allotypes might be linked to differences in the IgG-subclass profile of Ag-specific antibody responses generated in the context of HIV-1 vaccination ( 28 , 29 ). To pursue this, we developed novel PCR (Figure S1 in Supplementary Material) and ELISA protocols and combined them in a dual approach to determine the IgG1 allotype identity (G1m3 and/or G1m1) of clinical trial participants, using both human serum and mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…MAPPs has successfully been applied in a range of mechanistic studies, to interrogate the effect of PTMs (15), folding (12), and aggregation on antigen presentation (5). The technology has also been proven valuable for comparing the antigen presentation across different APC cell types (16,20), for determining naturally presented sequence regions of IVIg (19), and for evaluating the potential of human IgG1 allotypes to stimulate T cell responses in donors matched for homologous and heterologous IgG1 allotypes (18). As the MAPPs assay has shown the capacity to differentiate molecules regarding their content of potential T cell epitopes (6), the technology can also be useful to support candidate ranking and selection during early drug design and may contribute to the development of BPs with lower immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Some sequences cannot be efficiently identified due to technical reasons such as strong hydrophobicity preventing efficient elution from the chromatography column, poor ionization and fragmentation in the mass spectrometer, or degradation of the peptides due to extensive protease activity during cell culture. To rule out that regulatory T cell epitopes 167 and 289 were potentially missed in the experiment due to technical challenges, the researchers confirmed efficient detection via mass spectrometry (18). No significant responses against allotypic variants of trastuzumab were observed in allotypic mismatched T cells.…”
Section: Improving Mechanistic Understanding Of Principles Of Antigenmentioning
confidence: 93%
“…More recently, allotypes have been investigated for their potential role as immunogenic motifs in therapeutic antibodies. Surprisingly, it appears that allotypes act only as minor epitopes in monoclonal antibodies and do not appear to elicit acute rejection ( 12 ), although some studies have reported low levels of pre-existing circulating antibodies against allotypes of therapeutic monoclonals ( 13 , 14 ). A key pitfall of serological detection of allotypes is the difficulty of evaluating immunogenic responses to immunoglobulin isotypes expressed at low levels in serum, such as IgE and IgM, signified by a lack of known allotypes for these classes ( 8 ).…”
Section: Introductionmentioning
confidence: 99%